Effects of fish oil supplementation on prefrontal metabolite concentrations in adolescents with major depressive disorder: A preliminary 1H MRS study. (20th April 2016) - McNamara, Robert K.; Jandacek, Ronald; Rider, Therese; Tso, Patrick; Chu, Wen-Jang; Weber, Wade A.; Welge, Jeffrey A.; Strawn, Jeffrey R.; Adler, Caleb M.; DelBello, Melissa P.
Abstract : Objective : To use proton magnetic resonance spectroscopy ( 1 H MRS) to investigate the effects of fish oil (FO) supplementation on cortical metabolite concentrations in adolescents with major depressive disorder (MDD). Methods : Metabolite concentrations were determined by 1 H MRS in the anterior cingulate cortex and bilateral dorsolateral prefrontal cortex (DLPFC) of adolescents with MDD before and following 10-week open-label supplementation with low (2.4 g/day, n  = 7) or high (16.2 g/day, n  = 7) dose FO. Depressive symptom severity scores and erythrocyte fatty acid levels were also determined. Results : Baseline erythrocyte eicosapentaenoic acid (EPA) composition was positively correlated, and arachidonic acid (AA) and the AA/EPA ratio were inversely correlated, with choline (Cho) concentrations in the right DLPFC. Docosahexaenoic acid (DHA) composition was inversely correlated with myo -inositol (mI) concentrations in the left DLPFC. Erythrocyte EPA and DHA composition increased, and AA decreased, significantly following low-dose and high-dose FO supplementation. In the intent-to-treat sample, depressive symptom severity scores decreased significantly in the high-dose group (−40%, P  < 0.0001) and there was a trend in the low-dose group (−20%, P  = 0.06). There were no significant baseline–endpoint changes in metabolite levels in each voxel. In the low-dose group there were changes with large effect sizes, including a decrease in mI in the left DLPFC (−12%, P  = 0.18, d  = 0.8) and increases in glutamate + glutamine (Glx) (+12%, P  = 0.19, d  = 0.8) and Cho (+15%, P  = 0.08, d  = 1.2) in the right DLPFC. In the high-dose group, there was a trend for increases in Cho in the right DLPFC (+10%, P  = 0.09, d  = 1.2). Discussion : These preliminary data suggest that increasing the LC n -3 fatty acid status of adolescent MDD patients is associated with subtle changes in Glx, mI, and Cho concentrations in the DLPFC that warrant further evaluation in a larger controlled trial.